Philippines Quarterly Update, September 2011 : Solid Macroeconomic Fundamentals Cushion External Turmoil - World Bank Group (Manila, 2015)
The Philippines Quarterly Update provides an update on key economic developments and policies over the past three months. It also presents findings from recent World Bank work on the Philippines. As of September 2011 due to sluggish exports and government spending, economic growth was lower than expected. The Philippine economy continued to decelerate during the first half of 2011 as investment and exports contracted. Private consumption growth remained robust, rising by 5.4 percent in the first half of 2011 and contributing 3.6 percentage points to GDP growth in Q2 2011. A contraction in construction spending slowed down growth of fixed capital formation. On the supply side, the resilient services sector was the main source of growth. The Philippines' external position and macroeconomic fundamentals remain strong. Monetary policy remains accommodating, while the fiscal deficit is likely to fall below target. After a strong rebound in 2010, economic growth in 2011 is likely to remain around 5 percent with downside risks. The challenge for policymakers is to ensure that the Philippines continues to improve its competitiveness, while cushioning the economy from adverse external shocks.